Buildup of plasma oscillations during modeling the electromagnetic wave propagation - Pavlenko, I.V.; Melnyk, D.A.; Nakonechnyi, M.A.; Girka, I.A. (Вопросы атомной науки и техники, 2016)
A plane wave formation in plasmas is studied numerically by Finite Difference Time Domain (FDTD) solver. The electromagnetic wave is incident normally to the plane boundary between vacuum and isotropic homogeneous plasma. Different harmonics of the plane wave need different time to build up the oscillations in plasma. Therefore a vacuum waveform differs from plasma waveform not due to a difference in dispersions only. The formation of the plane wave in plasma is studied numerically for different points of the dispersion curve known from a plasma steady state theory. The study has to issue finally a numerical model of the plane wave source in plasmas to use it in the problems of plasma wave scattering, tunnelling and conversion. Формирование плоской волны в плазме изучается численно методом конечных разностей во временной области (КРВО). Электромагнитная волна падает перпендикулярно на плоскую границу раздела вакуума и однородной незамагниченной плазмы. Различным гармоникам плоской волны требуется различное время на раскачку плазменных колебаний. Поэтому различие между формами волны в вакууме и в плазме определяется не только различием в дисперсионных соотношениях. Формирование плоской волны в плазме изучается численно для различных точек дисперсионной кривой, которая известна из теории стационарной плазмы. Изучение проводится с целью создания численной модели источника плоской волны в плазме для её дальнейшего использования в задачах рассеяния, туннелирования и конверсии волн. Формування пласкої хвилі в плазмі вивчається числовим методом скінченних різниць у часовій області (СРЧО). Електромагнітна хвиля падає перпендикулярно на пласку межу поділу вакуума та однорідної незамагніченої плазми. Різні гармоніки пласкої хвилі потребують різного часу на розкачку плазмових коливань. Тому різниця між формами хвилі у вакуумі та в плазмі визначається не лише різницею в дисперсійних співвідношеннях. Формування пласкої хвилі в плазмі вивчається числовими методами для різних точок дисперсійної кривої, яка є відомою з теорії стаціонарної плазми. Дослідження проводиться з метою створення числової моделі джерела пласкої хвилі в плазмі для подальшого її використання в задачах розсіяння, тунелювання та конверсії хвиль.